Multiple Peptide Resistance Factor (MprF)-mediated Resistance of Staphylococcus aureus against Antimicrobial Peptides Coincides with a Modulated Peptide Interaction with Artificial Membranes Comprising Lysyl-Phosphatidylglycerol - Andrä, Jörg (American Society for Biochemistry and Molecular Biology, 2011)
Modification of the membrane lipid phosphatidylglycerol (PG) of Staphylococcus aureus by enzymatic transfer of a l-lysine residue leading to lysyl-PG converts the net charge of PG from −1 to +1 and is thought to confer resistance to cationic antimicrobial peptides (AMPs). Lysyl-PG synthesis and translocation to the outer leaflet of the bacterial membrane are achieved by the membrane protein MprF. Consequently, mutants lacking a functional mprF gene are in particular vulnerable to the action of AMPs. Hence, we aim at elucidating whether and to which extent lysyl-PG modulates membrane binding, insertion, and permeabilization by various AMPs. Lysyl-PG was incorporated into artificial lipid bilayers, mimicking the cytoplasmic membrane of S. aureus. Moreover, we determined the activity of the peptides against a clinical isolate of S. aureus strain SA113 and two mutants lacking a functional mprF gene and visualized peptide-induced ultrastructural changes of bacteria by transmission electron microscopy. The studied peptides were: (i) NK-2, an α-helical fragment of mammalian NK-lysin, (ii) arenicin-1, a lugworm β-sheet peptide, and (iii) bee venom melittin. Biophysical data obtained by FRET spectroscopy, Fourier transform infrared spectroscopy, and electrical measurements with planar lipid bilayers were correlated with the biological activities of the peptides. They strongly support the hypothesis that peptide-membrane interactions are a prerequisite for eradication of S. aureus. However, degree and mode of modulation of membrane properties such as fluidity, capacitance, and conductivity were unique for each of the peptides. Altogether, our data support and underline the significance of lysyl-PG for S. aureus resistance to AMPs.